Medical legal partnership and health informatics impacting child health: Interprofessional innovations. - Gilbert, Amy Lewis; Downs, Stephen M. (Journal of Interprofessional Care, 2015)
Dramatic differences in health are closely related to degrees of social and economic disadvantage. Poverty-induced hardships such as food insecurity, utility shut-offs, and substandard housing, all have the potential to negatively impact the health of families. In an effort to better address social determinants of health in pediatric primary health care settings using the Medical Legal Partnership (MLP) model of health care delivery, an interprofessional team of investigators came together to design an innovative process for using computerized clinical decision support to identify health-harming legal and social needs, improve the delivery of appropriate physician counseling, and streamline access to legal and social service professionals when non-medical remedies are required. This article describes the interprofessional nature of the MLP model itself, illustrates the work that was done to craft this innovative health informatics approach to implementing MLP, and demonstrates how pediatricians, social workers and attorneys may work together to improve child health outcomes.